PROSPECTS FOR IMPROVING PRODUCT QUALITY - Akbarjon Umarov; Jamshid Yuldashev (European Science Publishing, 2024)
This article discusses the factors and necessary measures to improve product quality, develop competitive products, and achieve success in the market. Various factors such as innovative new equipment and technologies, improvement of materials and raw materials, employee training, and quality control are discussed in detail.
Keywords: Product, quality, technologies, certification, efficiency.